2023
DOI: 10.1002/jum.16194
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Based Machine Learning Approach for Detection of Nonalcoholic Fatty Liver Disease

Abstract: Objectives-Current diagnosis of nonalcoholic fatty liver disease (NAFLD) relies on biopsy or MR-based fat quantification. This prospective study explored the use of ultrasound with artificial intelligence for the detection of NAFLD.Methods-One hundred and twenty subjects with clinical suspicion of NAFLD and 10 healthy volunteers consented to participate in this institutional review board-approved study. Subjects were categorized as NAFLD and non-NAFLD according to MR proton density fat fraction (PDFF) findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Liver ultrasound scans are a standard non-invasive diagnostic tool for chronic liver diseases, including MASLD, but are influenced by examiner subjectivity and exhibit reduced sensitivity when the liver contains less than 20–30% fat [43] . Limited studies on AI's application for predicting and classifying MASLD patients indicate promising results with excellent AUROC scores [44] , [45] , [46] . Additionally, ML algorithms integrated with transient elastography (TE) have been employed to predict liver fibrosis and MASLD in large clinical trial/cohort studies [47] , [48] , [49] .…”
Section: Big Data Classes and Their Utility In Masld Researchmentioning
confidence: 99%
“…Liver ultrasound scans are a standard non-invasive diagnostic tool for chronic liver diseases, including MASLD, but are influenced by examiner subjectivity and exhibit reduced sensitivity when the liver contains less than 20–30% fat [43] . Limited studies on AI's application for predicting and classifying MASLD patients indicate promising results with excellent AUROC scores [44] , [45] , [46] . Additionally, ML algorithms integrated with transient elastography (TE) have been employed to predict liver fibrosis and MASLD in large clinical trial/cohort studies [47] , [48] , [49] .…”
Section: Big Data Classes and Their Utility In Masld Researchmentioning
confidence: 99%
“…One way to overcome this is through implementation of AI for analysis of routine ultrasound imaging in CF which could provide a way to improve standardization and decrease heterogeneity in the interpretation of results. Indeed, the application of AI for ultrasound images of the liver is under intense study at this time and was recently demonstrated to be excellent for detection of steatotic liver disease 59 …”
Section: New Approaches To Study Cf Liver Diseasementioning
confidence: 99%
“…Indeed, the application of AI for ultrasound images of the liver is under intense study at this time and was recently demonstrated to be excellent for detection of steatotic liver disease. 59…”
Section: New Approaches To Study Cf Liver Diseasementioning
confidence: 99%
“…AI has been commonly used in clinical practice in many other ways nowadays. For instance, in a recent prospective study conducted in the United States in 2023, an ultrasound-based machine learning model using AI was used to detect metabolic dysfunction-associated steatotic liver disease (MASLD, formerly known as non-alcoholic fatty liver disease {NAFLD}) [ 14 , 15 ]. This machine learning device using ultrasound and AI reported high positive predictive value and specificity for detecting MASLD in high-risk patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%